Recommendations and practical guidance for performing and reporting validation studies according to the universal standard for the validation of blood pressure measuring devices by the Association for the Advancement of Medical Instrumentation/European Society of Hypertension/International Organization for Standardization (AAMI/ESH/ISO) - McManus, R; European Society of Hypertension Working Group on Blood Pressure Monitoring (Lippincott, Williams & Wilkins, 2019)
This statement by the European Society of Hypertension Working Group on Blood Pressure Monitoring (ESH) provides practical guidance for investigators performing validation studies of blood pressure measuring devices according to the Association for the Advancement of Medical Instrumentation/ESH/ International Organization for Standardization (ISO) Universal Standard (ISO 81060-2:2018). This statement provides: (i) a list of key recommendations for validation studies according to the Universal Standard, (ii) practical stepwise guidance for researchers performing validation studies, (iii) a checklist for authors and reviewers of such studies.